Sustainability of evidence-based primary care programs in Abu Dhabi: impact of COVID-19 - Baynouna Alketbi, Latifa; Nagelkerke, Nico; Abdelbaki, Hanan (Frontiers in Health Services, 2025)
IntroductionThe Abu Dhabi Ambulatory Healthcare Services (AHS) implemented the Chronic Disease Care (CDC) and Patient-Centered Medical Home (PCMH) programs. This study describes the implementation and integration of these two programs into the operations of AHS centers and assesses their long-term sustainability.MethodThis retrospective cohort study included all AHS centers. The sustainability of both programs was assessed twice yearly using the NCQA self-assessment audit and the CDC system audit. The care outcomes were measured through routinely collected Key Performance Indicators (KPIs) at multiple data collection points in 2018, 2021, and 2022. The study period included the COVID-19 period, providing an opportunity to examine the effect of pre-pandemic program scores on centers' performance during the pandemic. The KPIs are categorized into clinical, preventive, and utilization outcomes.ResultsLinear regression showed that the key performance indicator (KPI) for the best-performing centers had significantly higher PCMH scores, B = 0.447, p = 0.03, with no effect on the centers' financial revenue, B = 0.209, p = 0.29. Similarly, using univariate linear regression, a higher chronic disease care program assessment at the end of 2022 was significantly associated with centers performing better in clinical KPI, B = 0.480, p = 0.013. The Chronic Diseases Program assessment at the end of 2022 was as well positively and significantly associated with higher performance of centers regarding the NCQA PCMH standards, B = 0.647, p < 0.001. Pearson correlation analysis indicated significant correlations between clinical and preventive KPI achievements and the 2022 PCMH and CDC scores.ConclusionThe AHS centers successfully implemented both programs sustainably. The study findings highlight areas for sustainability research that demonstrate the value of sustainable interventions.